Breast-feeding duration and children’s nutritional status at age 12-24 months - Susilowati Susilowati; Kusharisupeni Kusharisupeni; Sandra Fikawati; Kusdinar Achmad (Indonesian Pediatric Society, 2010)
Background Relation between breast-feeding duration and children’s nutritional status is still a controversy. Positive as well as negative relation were shown. This study aimed to support this current issue on breast feeding duration and nutritional status of children aged 12-24 months.Objective To analyze relationship between breast-feeding duration and nutritional status of children aged 12-24 months.Methods A cross sectional study was conducted with 246 proportional stratified random coupled samples (mothers and weaned children) with inclusion criteria: normal birth weight, full-term delivery and no physical and psychological problems. Data from children were measured using Seca® digital weight scale, wooden length board, while data from mothers were collected through 1x24 Hours Food Recall Form, and a questionnaire on mother’s knowledge.Results The average of breast-feeding duration was 15 months. The prevalence of malnutrition was quite low (<10%), but the prevalence of stunting was high enough (20.7%) while wasting was moderately high (10.6%). Breast-feeding duration was significantly associated to children’s nutritional status (height-for-age index and weight-for-height index). The highest correlation was found in height-for-age index (r = 0.403). Regression model revealed that breast-feeding duration, exclusive breast-feeding, diarrhea, working mother, mother’s knowledge, energy intake, and protein intake were independently associated with children’s nutritional status.Conclusions As this study found that the average of breast-feeding duration was 15 months and there was a significant association between breast-feeding duration and nutritional status (height-for-age index) of children 12-24 months old, thus these findings strengthen the recommendation of WHO to continue breast feeding up to 2 years old. [Paediatr Indones. 2010;50:56-61].